2017
DOI: 10.1073/pnas.1709584114
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal increases local species richness and reduces spatial turnover of tropical tree seedlings

Abstract: Dispersal is thought to be a key process underlying the high spatial diversity of tropical forests. Just how important dispersal is in structuring plant communities is nevertheless an open question because it is very difficult to isolate dispersal from other processes, and thereby measure its effect. Using a unique situation, the loss of vertebrate seed dispersers on the island of Guam and their presence on the neighboring islands of Saipan and Rota, we quantify the contribution of vertebrate seed dispersal to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 50 publications
2
61
0
Order By: Relevance
“…Dispersal thus tends to erase the spatial boundaries between zones, and to homogenise species composition. This recovers results from metacommunity theory showing that dispersal decreases beta‐diversity among communities (Mouquet & Loreau ; Leibold et al ), a theoretical prediction that is supported by empirical studies (Forbes & Chase ; Kneitel & Miller ; Simonis & Ellis ; Wandrag et al ). In nature, the absence of clear discontinuities in species composition along spatial environmental gradients, as observed in plant species along altitudinal gradients (Lieberman et al ; Vazquez & Givnish ) or in marine benthic organisms along depth gradients (Smale ), might thus reflects either a truly individualistic organisation or the effects of dispersal blurring the boundaries of discrete communities.…”
Section: Discussionsupporting
confidence: 84%
“…Dispersal thus tends to erase the spatial boundaries between zones, and to homogenise species composition. This recovers results from metacommunity theory showing that dispersal decreases beta‐diversity among communities (Mouquet & Loreau ; Leibold et al ), a theoretical prediction that is supported by empirical studies (Forbes & Chase ; Kneitel & Miller ; Simonis & Ellis ; Wandrag et al ). In nature, the absence of clear discontinuities in species composition along spatial environmental gradients, as observed in plant species along altitudinal gradients (Lieberman et al ; Vazquez & Givnish ) or in marine benthic organisms along depth gradients (Smale ), might thus reflects either a truly individualistic organisation or the effects of dispersal blurring the boundaries of discrete communities.…”
Section: Discussionsupporting
confidence: 84%
“…Tawa Beilschmiedia tawa also appears to suffer from extremely low dispersal at some mainland sites (<10% of seeds captured below parent canopies had passed through a bird at three North Island sites; Silberbauer, ), although eight other studies on seed dispersal quantity in mainland New Zealand have found adequate dispersal rates (Kelly et al., ; Pegman, Perry, & Clout, ). On the Balearic Islands, introduced carnivorous mammals have indirectly lowered seedling recruitment of a perennial shrub by driving its mutualistic partner extinct (Traveset & Riera, ), while on Guam, the near‐total loss of frugivorous birds caused by the exotic brown tree snake ( Boiga irregularis ) may have caused a 61%–92% decline in seedling recruitment for two plant species (Rogers et al., ) and a reduction in seedlings of all tree species reaching canopy gaps away from parent trees (Wandrag, Dunham, Duncan, & Rogers, ). Whether the reduced dispersal we have recorded results in lowered recruitment for hinau depends on hinau's reliance on avian dispersal for improved germination (e.g., by gut passage, see Robertson, Trass, Ladley, & Kelly, ) and escape from disproportionate density‐ and distance‐dependent mortality beneath parent canopies (i.e., Janzen–Connell effects, see Comita et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…; Wandrag et al . ). In these situations, a variety of impacts on seedlings of trees has been reported, including reduced diversity, greater spatial aggregation around parent trees and either high or lower densities depending on plant species, with greatest reductions in larger‐seeded species.…”
Section: Fauna‐mediated Processes That Drive Revegetation Dynamicsmentioning
confidence: 97%
“…Second, the significance of animalplant interactions to plant recruitment has been strongly highlighted by recent reviews and investigations of 'empty forests'remnant mature forests where hunting or other impacts have extirpated many vertebrate animals in recent decades, while the habitat otherwise remains little-disturbed (Harrison et al 2013;Kurten 2013;Kurten et al 2015;Neuschulz et al 2016;Wandrag et al 2017). In these situations, a variety of impacts on seedlings of trees has been reported, including reduced diversity, greater spatial aggregation around parent trees and either high or lower densities depending on plant species, with greatest reductions in largerseeded species.…”
Section: Fauna-mediated Processes That Drive Revegetation Dynamicsmentioning
confidence: 99%